Perbedaan Tingkat Aspirasi dan Persepsi tentang Belajar Matematika antara Siswa Berlatar Budaya Minangkabau dan Batak - Herman Nirwana (Universitas Negeri Malang, 2016)
This study focuses on finding out the differences of perception and level of aspiration among students of different gender and cultural backgrounds. Employing a survey design, this study involved 523 students of senior high schools. Their responses to questionnaires were anayzed using t-test. The findings suggest that in terms of gender and cultural backgrounds no difference was found in the students perception and level of aspiration concerning mathematics learning.